Pemulihan Lahan Pertanian Akibat Banjir Lahar Dingin Gunung Marapi Di Jorong Aur Nagari Barulak Kecamatan Tanjuang Baru - Alexander Syam; Ika Anggraeni; Nisye Frisca (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Mount Marapi cold lava flood disaster that struck Jorong Aur, Nagari Barulak, Tanjuang Baru District, Tanah Datar Regency, caused significant damage to agricultural land and the community's irrigation system. This community service program aim store store agricultural land function through has eriesofactivities, including mapping and identifying affected land, clearing and physically rehabilitating the land, and repairing irrigation channels. The implementation method was a participatory approach involving the community, farmer groups, and the village government. The results indicate that most of the land buried by volcanic material was successfully cleared and can be re-cultivated, the main irrigation channel is functional, and the community has experienced increased capacity in post-disaster agricultural management. In addition to physical outcomes, this activity also resulted in the implementation of soil biorehabilitation with organic fertilizer. This program contributes to improving food security, strengthening mutual cooperation, and raising community awarenessof the importance of sustainable land management after a disaster.